Pengembangan Pemberdayaan Ekonomi Pesantren Melalui Pengelolaan Sampah Secara Berkelanjutan - Jauhariyah, Nur Anim; Susanti, Nawal Ika; Mahmudah, Mahmudah; Nurus Sofa, Fatiha Indana; Qohar, M Khafidul (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is 1) Segregation of waste is carried out from the start when the waste is produced; 2) Motivating students in the movement to start sorting waste starting with me; 3) Motivating education unit managers to provide separate bins according to the type of waste. This service was carried out in 16 education units and TPS3R Kalisurodi under the auspices of the Darussalam Pondok Pesantren Blokagung Banyuwangi. The mentoring method used is the Asset Based Communities Development (ABCD) approach. The results of the service show that there has been an increase in knowledge about increasing knowledge related to 1) Types of organic, inorganic waste, and hazardous and toxic materials; 2) Reusable & Recyclable materials (selling value); 3) Differences between Kitchen Waste and Garden Waste M 4) various examples of hazardous and toxic materials (B3); 5) Impact if waste is not managed on health; 6) Reasons why waste must be managed; 7) Stages of waste management in Islamic boarding schools and educational units; 8) Manufacture of individual composters; 8) Know the BSF cultivation cycle; 9) Recognizing that it is necessary to separate the impact from the source to solve the segregation problem at the TPS; 10) Knowing that there is a need for behavior change in all individual components in Islamic boarding schools and education units as a solution to solving waste problems. This assistance emphasizes that in implementing Islamic boarding schools' economic empowerment through sustainable waste management, a joint committee is required between all components in the foundation, education units, and TPS3R Kalisuro waste management to sort waste from sources, form waste banks in each education unit, and provide adequate infrastructure facilities for management